2015
DOI: 10.7752/jpes.2015.02033
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:The aim of this study was to analyse the team-members cooperation in basketball by using centrality metrics of network. Different ages were compared in this study. Forty players (10 players of under-14; 10 players of under-16; 10 players of under-18 and 10 players in amateurs with more than 20 years) voluntarily participated in this study. A total of 326 units of attack were generated based on the team-members interactions and then converted in final graphs. The one-way ANOVA for the factor tactical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Further, they outperformed non-selected players on this position with respect to shooting. The central role of the point guard in a basketball teams' attack has been confirmed for youth and senior basketball by in-depth analyses of passing sequences (Clemente et al, 2015;Korte and Lames, 2018). The results of the present study reflect this centrality as selected players are more involved in their teams' offensive game play.…”
Section: Diagnostic Validity (Objective 2)supporting
confidence: 71%
“…Further, they outperformed non-selected players on this position with respect to shooting. The central role of the point guard in a basketball teams' attack has been confirmed for youth and senior basketball by in-depth analyses of passing sequences (Clemente et al, 2015;Korte and Lames, 2018). The results of the present study reflect this centrality as selected players are more involved in their teams' offensive game play.…”
Section: Diagnostic Validity (Objective 2)supporting
confidence: 71%
“…Alternatively, player roles within a team may reflect the team strategy for each particular game. Indeed, Clemente et al [ 29 ] and Mexas et al [ 30 ] observed individual performance in basketball to be reflective of the player’s role. Point guards were found to be the most prominent position during offensive organization [ 29 ], while perimeter players were observed to be primarily responsible for the majority of offensive efforts relative to post-players [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Clemente et al [ 29 ] and Mexas et al [ 30 ] observed individual performance in basketball to be reflective of the player’s role. Point guards were found to be the most prominent position during offensive organization [ 29 ], while perimeter players were observed to be primarily responsible for the majority of offensive efforts relative to post-players [ 30 ]. Post-players in comparison were observed to be the least prominent position during offensive organization with their primary role to receive the ball and shoot [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation